A Chinese Herbal Decoction, Dang Gui Bu Xue Tang, Prepared from Radix Astragali and Radix Angelicae sinensis, Ameliorates Insulin Resistance Induced by A High-Fructose Diet in Rats. (14th February 2011) - Liu, I-Min; Tzeng, Thing-Fong; Liou, Shorong-Shii
Abstract : Dang Gui Bu Xue Tang (DBT), a Chinese medicinal decoction contains Radix Angelicae sinensis (Danggui) and Radix Astragali (Huangqi) at a ratio of 1 : 5, is used commonly for treating women's ailments. This study was conducted to explore the effects of this preparation on insulin resistance in rats fed with 6-week diet containing 60% fructose. Similar to the action of rosiglitazone (4 mg kg -1 per day by an oral administration), repeated oral administration of DBT (2.5 g kg -1 per day) for 14 days was found to significantly alleviate the hyperglycemia but made no influence on plasma lipid profiles nor weight gain in fructose chow-fed rats. Also, the higher degree of insulin resistance as measured by homeostasis model assessment of basal insulin resistance in fructose chow-fed rats was significantly decreased by repeated DBT treatment. DBT displays the characteristic of rosiglitazone by increasing the whole-body insulin sensitivity in fructose chow-fed rats after 2-week treatment, as evidenced by the marked elevation of composite whole-body insulin sensitivity index during the oral glucose tolerance test. DBT improves insulin sensitivity through increased post-receptor insulin signaling mediated by enhancements in insulin receptor substrate-1-associated phosphatidylinositol 3-kinase step and glucose transporter subtype 4 translocation in soleus muscles of animals exhibiting insulin resistance. DBT is therefore proposed as potentially useful adjuvant therapy for patients with insulin resistance and/or the patients who wish to increase insulin sensitivity.